ANALISIS FENOMENA BULLYING DI DUNIA PENDIDIKAN PERSPEKTIF TEORI EKOLOGI BRONFENBRENNER - Luthfi Syifa' Fauziyah; Fifi Nur Lynda Febriyani; Putri Komala Sari; Mohamad Ali (Program Studi Manajemen Pendidikan Islam, 2025)
Bullying is an aggressive act that is repeatedly carried out by an individual or group against other more vulnerable individuals, which includes physical, verbal, and relational forms. This phenomenon not only has an impact on the mental health and social development of victims but also creates an educational environment that is unsafe and not conducive to learning. This study uses a library research method with a qualitative descriptive approach. The data analyzed included books, articles, journals, and reports related to bullying. Bronfenbrenner's Ecological Theory is used to understand how the different layers of the environment of microsystems, mesosystems, ecosystems, macrosystems, and chronosystems influence bullying behavior. The results of the analysis show that bullying behavior is not only influenced by internal factors of individuals but also by family environment, school culture, peer pressure, and the influence of media and social policies. This study found that a multidimensional approach to prevention and intervention is essential for dealing with bullying. Strategies that involve families, schools, and communities are needed to create an environment that supports the positive development of children. By understanding the relationship between these ecological layers, this study offers more holistic policy recommendations to reduce the incidence of bullying in educational settings. This research is expected to contribute to efforts to prevent bullying and create a more inclusive and safe educational environment